Eco-Enzyme Applications for Biosecurity and Sanitation on Goat Farm in Namorambe District, Deli Serdang Regency - patriani, peni patriani (Talenta Publisher Universitas Sumatera Utara, 2022)
Deli Serdang is a district that has the highest population of sheep and goats. The maintenance system is in the semi-intensive category so it can be categorized as an animal husbandry livelihood. An independent livestock business namely Al-Hafidz sheep and goat farming is located in Sidirejo Village, Namorambe District, Deli Serdang Regency. Problems in the Al-Hafidz farmer group are the decline in livestock health and poor sanitation of the cage. This problem can affect the health of livestock, especially skin diseases and can be transmitted to the breeder. The purpose of this community service activity is to improve biosecurity and cage sanitation using eco enzymes. Activities are carried out by making natural disinfectants that are easy and do not require expensive costs, such as eco-enzymes. Kitchen waste can be used as an ingredient to make Eco-Enzymes. Eco Enzyme is very useful as an insect repellent, house cleaning flies and equipment, insecticide, an antiseptic or natural antibacterial. The methods used are training, counseling, and assistance to farmer groups. The results achieved are increased knowledge of farmers regarding the manufacture of eco-enzymes as cage biosecurity by utilizing fruit peel waste, reducing household waste pollution, and reducing the cost of purchasing disinfectants.